300 Million Clicks and Political Engagement via Facebook in the 2016 American Presidential Election: How Online Activity Changes Across Time and Sources. Issue 6 (2nd November 2018) - Silva, David E.; Hutchens, Myiah J.; Donaway, Rebecca R.; Beam, Michael A.
Abstract : News media set an agenda of salient topics for the public, especially during a presidential election. The importance of the media has not decreased with the increase in media choice and growth of social network sites such as Facebook. Instead, social media provide additional opportunities for scholars to observe how individuals are following news content and engaging politically. News content is often distributed through social media platforms where citizens respond and react to cues about the importance of events or stories. Through the collection and analysis of all Facebook posts and their metadata from 8 prominent Facebook pages, this study tracks the changes in Facebook users' engagement over the course of the 2016 campaign using multilevel spline regression. We extend prior research by examining traditional campaign events as well as partisan scandals across a variety of organization types. Engagement does vary from July to November, and we find source characteristics drive attention at specific phases of the campaign.